2020
DOI: 10.9734/cjast/2020/v39i2830947
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Lethal Dose Determination for Gamma Rays and EMS Induced Mutagenesis in TMV7 and SVPR1 Sesame (Sesamum indicum L.) Varieties

Abstract: In the present study two sesame varieties viz., TMV7 and SVPR1 were treated with varying doses of gamma rays (250, 300, 350, 400 and 450 Gy) and Ethyl Methane Sulphonate (EMS) of different concentrations viz.,0.20, 0.40 and 0.60%. The seed germination percentage was greatly affected by mutagenic treatment of gamma rays and EMS which showed a negative dose dependent relationship in both the varieties. The expected LD50 values were calculated through probit analysis. The LD50 values for TMV7 and SVPR1 were fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…GAM 8. However, it was reported that LD50 value varies with species, genotypes, varieties, types of mutagen and nature of treatment and procedure (Parthasarathi et al, 2020). In previous finding showed that LD50 value as 250 Gy of gamma rays in balck gram var.…”
Section: Resultsmentioning
confidence: 99%
“…GAM 8. However, it was reported that LD50 value varies with species, genotypes, varieties, types of mutagen and nature of treatment and procedure (Parthasarathi et al, 2020). In previous finding showed that LD50 value as 250 Gy of gamma rays in balck gram var.…”
Section: Resultsmentioning
confidence: 99%